2012
DOI: 10.17925/eoh.2012.08.02.97
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Educational Needs and Enhancing Adherence of Patients Receiving Oral Cancer Agents Through Use of the MASCC Oral Agent Teaching Tool©

Abstract: The challenge of patient education traditionally is a responsibility of nurses. The nursing process of assessing, planning, implementing and evaluating is never more appropriate than when teaching patients and families about cancer treatments. In the past, as patients prepared for traditional IV (intravenous) treatment, nurses had a 'captured audience' to teach and the opportunity to then reinforce repeated verbal instructions and written materials, slowly and thoroughly reviewing procedures and potential prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
(11 reference statements)
0
13
0
Order By: Relevance
“… 22 Additionally, 20%–30% of chemotherapy agents in the development pipeline will be administered orally. 23 Recent studies of the oral chemotherapy medication use process identified key vulnerabilities, including patient education about drug handling and adverse effects, prescription writing, monitoring, and toxicity management, and highlighted the need to adopt rigorous safety standards. 24 26 However, adoption of these practice standards has been lagging for the oral chemotherapy agents.…”
Section: Resultsmentioning
confidence: 99%
“… 22 Additionally, 20%–30% of chemotherapy agents in the development pipeline will be administered orally. 23 Recent studies of the oral chemotherapy medication use process identified key vulnerabilities, including patient education about drug handling and adverse effects, prescription writing, monitoring, and toxicity management, and highlighted the need to adopt rigorous safety standards. 24 26 However, adoption of these practice standards has been lagging for the oral chemotherapy agents.…”
Section: Resultsmentioning
confidence: 99%
“…Prior publications (Kav et al, 2010;Rittenberg, 2012) have promoted the MOATT as standard-of-care education, but randomized trials have yet to be published regarding the tool's efficacy. Additional testing of innovative multimethod strategies, including nurse-led instruction, medication prompting, and reinforcement, with monitoring of self-care behaviors and symptoms, has been recommended to increase medication adherence (Schneider, 2012;Schneider, Hess, & Gosselin, 2011;Weingart et al, 2012), improve management of symptoms (Moody & Jackowski, 2010), and optimize patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy “information about oral chemotherapy” consisted of five individual documents containing information extracted from the Australian website (eviQ.org.au), which is routinely used by Australian cancer institutions, and based on guidelines from the Multinational Association of Supportive Care in Cancer Oral Agent Teaching Tool (MOATT) 23 . Documents on how to manage the main five side‐effects from each OC in the study (in the product information) were based on the Symptom Management Toolkit, 24 with permission from the Michigan State University adapted to the Australian context by the researcher oncologist (IO) 22…”
Section: Methodsmentioning
confidence: 99%